Asynchronous Accumulation of Organic Carbon and Nitrogen in the Atlantic Gateway to the Arctic Ocean - Paulsen, Maria L.; Seuthe, Lena; Reigstad, Marit; Larsen, Aud; Cape, Mattias R.; Vernet, Maria (Frontiers in Marine Science, 2018)
Nitrogen (N) is the main limiting nutrient for biological production in the Arctic Ocean. While dissolved inorganic N (DIN) is well studied, the substantial pool of N bound in organic matter (OM) and its bioavailability in the system is rarely considered. Covering a full annual cycle, we here follow N and carbon (C) content in particulate (P) and dissolved (D) OM within the Atlantic water inflow to the Arctic Ocean. While POC, PON, and DOC accumulated in the surface waters from January to May, the DON-pool decreased substantially (Δ - 50 µg N L-1). The DON reduction was greater than the simultaneous reduction in DIN (Δ - 30 µg N L-1), demonstrating that DON is a valuable N-source supporting the growing biomass. While the accumulating POM had a C/N ratio close to Redfield, the asynchronous accumulation of C and N in the dissolved pool resulted in a drastic increase in the C/N ratio of DOM during the spring bloom. This is likely due to a combination of the reduction in DON, and a high release of carbon-rich sugars from phytoplankton, as 32% of the spring primary production was dissolved. Our findings thus caution calculations of particulate primary production from DIN drawdown. During post-bloom the DON pool increased 3-fold due to an enhanced microbial processing of organic matter and reduced phytoplankton production. The light absorption spectra of DOM revealed high absorption within the UV range during spring bloom indicating DOM with low molecular weight in this period. The ‘spring CDOM signal’ was not present in August and absorption in the winter months was low. Our results demonstrate that the change in ecosystem function (i.e. phytoplankton species and activity, bacterial activity and grazing) in different seasons is associated with strong changes in the C/N ratios and optical character of DOM and underpin the essential role of DON for the production cycle in the Arctic.